Burgerlike Ongehoorsaamheid - Heyns, Johan Adam (Verbum et ecclesia, 1991)
Civil Disobedience For a twofold reason civil disobedience is currently a well known phenomenon not only in South Africa but also in different countries in the rest of the world. Firstly because it is practised by more people more frequently as a means of solving political problems, and secondly because more people are justifying it on theological grounds. After an attempt at a satisfactory definition an analysis is made of civil disobedience from a social ethical perspective. Certain fundamental aspects then come under scrutiny and the principal background for civil disobedience is supplied. Having given a short critical evaluation the article ends with some positive guideliness.